Waterproof and decorative integrated reflective heat-insulating waterborne polyurethane exterior wall coating and preparation method thereof
By developing a waterproof and decorative integrated reflective and thermally insulated water-based polyurethane exterior wall coating, the problem of waterproofing and decoration in steps in traditional construction is solved, and the multifunctional performance of the paint and construction simplification are achieved.
Patent Information
- Application Number
- CN202510316496.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-18
AI Technical Summary
Traditional water-based coatings and waterproof coatings are different types of products, which lead to the need to perform waterproofing and decorative construction in steps during construction, which is complicated in operation.
Develop a waterproof and decorative integrated reflective and thermally insulated water-based polyurethane exterior wall coating. By reasonably preparing water-based polyurethane emulsion, fillers, modified particles, reflective thermal insulating color paste and other components, a coating with excellent decorative and waterproof performance is formed.
It realizes the integration of decoration and waterproofing of the paint, and has good corrosion resistance, stain resistance, aging resistance and reflection insulation properties, simplifies construction steps and reduces operational complexity.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of coatings, and in particular to a reflective water-insulating water-soluble polyurethane exterior wall coating with integrated waterproofing and decoration, and a preparation method thereof. Background Art
[0002] In recent years, with the intensification of the global energy crisis and the improvement of environmental awareness, the development of high-performance, environmentally friendly architectural coatings has become an important development direction for the coatings industry. Waterborne polyurethane coatings have gradually replaced traditional solvent-based coatings due to their excellent physical and chemical properties, such as good flexibility, chemical resistance and environmental protection, and have been widely used in building exterior walls, steel structures, public facilities and other fields.
[0003] As a kind of energy-saving material, reflective heat-insulating coating can effectively reflect infrared and visible light in sunlight, reduce the heat absorbed by the building surface, thereby reducing indoor temperature and saving air conditioning energy consumption. This type of coating not only helps to improve the energy efficiency of buildings, but also improves the comfort of living and working environments. However, traditional water-based coatings and waterproof coatings are different types of products. In the field of construction, they are divided into different construction processes such as waterproofing and decoration. Water-based coatings used for decoration do not have the sunlight reflection and heat insulation properties of waterproofing, energy saving and consumption reduction. Therefore, the usual construction steps are to apply waterproof coatings on the exterior walls and then apply water-based coatings for exterior wall decoration, which is more complicated.
[0004] Therefore, in order to effectively solve the above problems, the present application provides a waterproof and decorative integrated reflective water-based polyurethane exterior wall coating and a preparation method thereof. The water-based polyurethane exterior wall coating finally prepared by the present application not only has excellent decorative and waterproof integration performance, but also can maintain good corrosion resistance, stain resistance, aging resistance and reflective heat insulation performance, thereby meeting the existing consumers' demand for the multifunctional performance of exterior wall coatings, and avoiding the problem of the existing waterproof coating-decorative coating step-by-step construction, reducing construction operations, and therefore has very excellent application prospects. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present application provides a reflective water-insulating water-based polyurethane exterior wall coating with integrated waterproof decoration. The raw materials are, in terms of mass percentage, 30~40% water-based polyurethane emulsion, 20~30% filler, 8~12% modified particles, 3~6% reflective water-insulating color paste, 0.3~0.5% cellulose ether, 0.2~0.3% pH adjuster, 0.3~0.5% dispersant, 0.1~0.2% wetting agent, 0.3~0.5% defoamer, 0.3~0.5% rheological additive, 0.5~1% antifreeze agent, 2~2.5% film-forming additive, 0.3~0.6% mildew and antibacterial agent, and the balance is supplemented by deionized water.
[0006] As a preferred solution, the solid content of the aqueous polyurethane emulsion is 30-50%.
[0007] As a preferred solution, the solid content of the aqueous polyurethane emulsion is 35-45%.
[0008] As a preferred solution, the viscosity of the aqueous polyurethane emulsion is 300-2000 mPa·s, condition: 25°C.
[0009] As a preferred solution, the viscosity of the aqueous polyurethane emulsion is 800-1400 mPa·s, condition: 25°C.
[0010] As a preferred solution, the filler is at least one of barium sulfate, calcium carbonate, talc, kaolin and diatomaceous earth.
[0011] As a preferred solution, the filler is barium sulfate or talc.
[0012] As a preferred solution, the average particle size of the filler is 0.1-1 μm.
[0013] As a preferred solution, the average particle size of the filler is 0.2-0.6 μm.
[0014] As a preferred solution, the mass ratio of the aqueous polyurethane emulsion, filler and modified particles is (32-38): (22-26): (10-12).
[0015] As a preferred solution, the mass ratio of the aqueous polyurethane emulsion, filler and modified particles is (34-36): (23-25): (10-11).
[0016] As a preferred solution, the mass ratio of the aqueous polyurethane emulsion, filler and modified particles is 35:24:10.5.
[0017] As a preferred solution, the modified particles are modified titanium dioxide.
[0018] As a preferred solution, the preparation method of the modified titanium dioxide specifically comprises the following steps: S1: titanium dioxide and zinc chloride are mixed and added to a DMF solution, succinic anhydride is added, the temperature is raised to 70-75°C and the temperature is kept for 3-3.5 hours, after the reaction is completed, diethylamine is added to adjust the pH to 7.5-8, then dodecyl dimethyl benzyl ammonium bromide, polyethylene glycol 2000 and terephthalic acid are added, the temperature is raised to 110-120°C and the temperature is kept for 24-30 hours, the product is filtered, and the DMF solution is added. F is washed 2 to 3 times, and pre-reacted particles are obtained after drying; S2: the pre-reacted particles, 1,4-diaminobenzene, p-aminobenzoic acid and 2-methylimidazole are mixed and added to DMF, and stirred at 70-80°C and 200-300rpm for 16-20h; S3: the temperature is then raised to 100-110°C, and the reaction is kept warm for 14-16h. After the reaction is completed, the product is filtered, washed with DMF 2 to 3 times, and vacuum dried at 80-90°C for 6-8h. After completion, the product is obtained.
[0019] As a preferred solution, the mass ratio of titanium dioxide, zinc chloride and succinic anhydride is (2.3-2.6): (1.8-2.1): (1-1.2).
[0020] As a preferred solution, the mass ratio of titanium dioxide, dodecyldimethylbenzyl ammonium bromide, polyethylene glycol 2000 and terephthalic acid is (2.3-2.6): (0.2-0.25): (0.3-0.4): (2-2.5).
[0021] As a preferred solution, the mass ratio of the pre-reacted particles, 1,4-diaminobenzene, p-aminobenzoic acid and 2-methylimidazole is (2.1-2.4): (0.6-0.8): (0.2-0.4): (0.1-0.2).
[0022] As a preferred solution, the average particle size of the titanium dioxide is 5-10 nm.
[0023] As a preferred solution, the average particle size of the modified titanium dioxide is 500-600 nm.
[0024] In this application, the addition of the modified titanium dioxide prepared as above can effectively improve the reflective heat insulation performance of the exterior wall coating, and at the same time maintain excellent corrosion resistance and aging resistance. The modified titanium dioxide can form a composite particle with modified titanium dioxide as the surface particle and a multi-microporous skeleton as the main body inside through the construction of a multi-composite skeleton. The composite skeleton structure of the modified particles greatly improves the refractive index of the titanium dioxide particles. At the same time, because the skeleton structure greatly enhances the electron vibration effect of the surface modified titanium dioxide in the infrared light band, and enriches the electrons on the surface, the reflection efficiency of the modified titanium dioxide for near-infrared light is further enhanced, and the absorption of heat is greatly reduced. The more complex particle skeleton structure enhances the light scattering effect of the light wave on the surface and inside of the coating, greatly increases the length of the light penetration path, and reduces the light scattering energy penetrating into the interior of the coating, thereby enabling the exterior wall coating to obtain excellent reflective heat insulation performance.
[0025] On the other hand, modified titanium dioxide can form a good heterojunction structure under the premise of absorbing a small amount of light energy. The existence of the structure can greatly enhance the aggregation and stability of the oxidized molecules on the surface of the particles, thereby maintaining good impedance of active molecules and organic molecules during long-term use, thereby obtaining excellent corrosion resistance, stain resistance and aging resistance. The modified titanium dioxide can enhance its mutual connection with the polyurethane resin system through the action of the surface modified groups, thereby greatly enhancing the stability of the modified titanium dioxide in the system, greatly reducing the micropores of the modified particles in the system, and reducing the large gaps formed by the series connection of pores, thereby greatly enhancing the barrier effect of the exterior wall coating on moisture and active molecules, thereby maintaining excellent corrosion resistance and other properties.
[0026] As a preferred scheme, the preparation method of the reflective heat-insulating color paste specifically includes the following steps: S1: adding deionized water to a high-speed mixer, and then adding sodium polycarboxylate, cocamidopropyl betaine, defoamer BYK-066N and reflective heat-insulating pigment in sequence, stirring at a speed of 600-800 rpm for 15-20 minutes to ensure uniform dispersion, and then adding hydroxyethyl cellulose and sodium hydroxide solution to adjust the pH to 8-8.5, and then increasing the speed to 1200-1500 rpm to maintain high-speed dispersion for 40-60 minutes to ensure that the reflective heat-insulating pigment is fully dispersed to form a stable pre-dispersion liquid; S2: transferring the pre-dispersion liquid to a sand mill for sand milling for 80-100 minutes, and then transferring it to a mixing kettle to add polyurethane rheological additives, propylene glycol and thiabendazole, adjusting the stirring speed to 650-750 rpm, stirring for 20-30 minutes, and then filtering the mixed product through a 200-300 mesh sieve to remove large particle impurities, and sealing and storing.
[0027] As a preferred solution, the reflective heat-insulating pigment is at least one of titanium dioxide, cobalt chrome blue, cobalt blue, cobalt green, iron chrome black, titanium chrome brown, zinc iron yellow and titanium nickel yellow.
[0028] As a preferred solution, the mass ratio of the sodium polycarboxylate, cocamidopropyl betaine, reflective heat-insulating pigment, hydroxyethyl cellulose and sodium polyacrylate is (2-3): (0.5-1): (25-28): (2.5-3): (0.4-0.6).
[0029] As a preferred solution, the cellulose ether is a combination of hydroxyethyl cellulose and methyl hydroxyethyl cellulose.
[0030] As a preferred embodiment, the mass ratio of hydroxyethyl cellulose to methyl hydroxyethyl cellulose is (3-4): (1-1.2).
[0031] As a preferred solution, the pH regulator is at least one of ammonia water, triethanolamine, sodium hydroxide, 2-amino-2-methyl-1-propanol and triethylamine.
[0032] As a preferred solution, the pH regulator is ammonia water or sodium hydroxide.
[0033] As a preferred solution, the dispersant is at least one of polycarboxylate sodium salt, polycarboxylate ammonium salt, lauryl alcohol polyoxyethylene ether, cetearyl alcohol polyoxyethylene ether and coconut oil betaine.
[0034] As a preferred solution, the dispersant is coconut oil based betaine.
[0035] As a preferred solution, the wetting agent is polyether-modified polysiloxane or polysiloxane.
[0036] As a preferred solution, the wetting agent is polysiloxane.
[0037] As a preferred solution, the defoaming agent is at least one of BYK-024, BYK-025, BYK-088, BYK-1790 and BYK-066N.
[0038] As a preferred solution, the defoaming agent is BYK-066N.
[0039] As a preferred solution, the rheological additive is a composition of acrylic acid and polyurethane.
[0040] As a preferred solution, the mass ratio of the acrylic acid to the polyurethane is (2-2.5):(5.5-6).
[0041] As a preferred solution, the mass ratio of acrylic acid to polyurethane is 2.5:5.8.
[0042] As a preferred solution, the antifreeze agent is at least one of polyethylene glycol, propylene glycol, glycerol, diethylene glycol and a nonionic surfactant.
[0043] As a preferred solution, the antifreeze agent is a composition of propylene glycol and non-ionic.
[0044] As a preferred solution, the mass ratio of propylene glycol to diethylene glycol is (3-4):(1.2-1.5).
[0045] As a preferred solution, the mass ratio of propylene glycol to diethylene glycol is 3.6:1.4.
[0046] As a preferred solution, the film-forming aid is a combination of dodecyl alcohol ester and hexadecanol ester.
[0047] As a preferred solution, the mass ratio of the dodecanol ester to the hexadecanol ester is (6-8):(1.5-2.5).
[0048] As a preferred solution, the mildew and fungicide is at least one of thiabendazole, dithiocyanomethane, zinc pyridinethione, benzmethylisothiazolinone and methylisothiazolinone.
[0049] As a preferred solution, the mildew and antibacterial agent is a combination of benzmethylisothiazolinone and methylisothiazolinone.
[0050] As a preferred solution, the mass ratio of the benzmethylisothiazolinone to methylisothiazolinone is (1.5-2):(0.5-0.8).
[0051] The second aspect of the present application provides a method for preparing the above-mentioned reflective heat-insulating water-based polyurethane exterior wall coating with integrated waterproof decoration, which specifically comprises the following steps: S1: adding deionized water to a mixing container, adding filler, modified particles and reflective heat-insulating color paste in sequence, stirring continuously for 30 to 40 minutes to ensure uniform dispersion, adding cellulose ether, pH adjuster, dispersant, wetting agent and defoamer, continuing stirring for 15 to 20 minutes, increasing the speed to 1200 to 1500 rpm, and maintaining high-speed dispersion for 30 to 60 minutes to ensure full dispersion to form a stable pre-dispersion liquid; S2: then slowly adding water-based polyurethane emulsion, while adding at 400 to 500 Stir at a speed of rpm to ensure uniform mixing; S3: add rheological additives, antifreeze agents, film-forming additives and mildew and antibacterial agents, adjust the stirring speed to 650-750rpm, stir for 20-30min, then filter the mixed product through a 100-200 mesh sieve to remove large particles of impurities, and divide the filtered coating into clean and dry containers and store them in a sealed container.
[0052] The beneficial effects of this application are: 1. The present application provides a waterproof, decorative, reflective, and water-insulating water-soluble polyurethane exterior wall coating, which not only has excellent decorative and waterproof integration properties, but also maintains good corrosion resistance, stain resistance, aging resistance, and reflective and heat-insulating properties, thereby meeting the multifunctional performance requirements of existing consumers for exterior wall coatings, and avoiding the problem of the existing waterproof coating-decorative coating step-by-step construction, reducing construction operations, and therefore has very excellent application prospects.
[0053] 2. The present application provides a reflective water-insulating polyurethane exterior wall paint with integrated waterproof decoration. The added modified titanium dioxide can form composite particles with modified titanium dioxide as surface particles and a multi-microporous skeleton as the main body inside through the construction of a multi-composite skeleton. The composite skeleton structure of the modified particles greatly improves the refractive index of the titanium dioxide particles. At the same time, because the skeleton structure greatly enhances the electron vibration effect of the surface modified titanium dioxide in the infrared light band, and enriches the electrons to gather on the surface, the reflection efficiency of the modified titanium dioxide for near-infrared light is further enhanced, and the absorption of heat is greatly reduced. The more complex particle skeleton structure enhances the light scattering effect of light waves on the surface and inside of the paint, greatly increases the length of the light penetration path, and reduces the light scattering energy penetrating into the paint, thereby enabling the exterior wall paint to obtain excellent reflective and heat-insulating properties.
[0054] 3. The present application provides a reflective water-insulating polyurethane exterior wall coating with integrated waterproof decoration. The added modified titanium dioxide can form a good heterojunction structure while absorbing a small amount of light energy. The existence of the structure can greatly enhance the aggregation and stability of the oxidized molecules on the surface of the particles, thereby maintaining good impedance of active molecules and organic molecules during long-term use, thereby obtaining excellent corrosion resistance and aging resistance. DETAILED DESCRIPTION
[0055] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0056] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0057] Example 1 Example 1 The first aspect provides a reflective heat-insulating water-based polyurethane exterior wall coating with integrated waterproof decoration. The raw materials are, in terms of mass percentage, 40% water-based polyurethane emulsion, 30% filler, 15% modified particles, 4.5% reflective heat-insulating color paste, 0.4% cellulose ether, 0.22% pH adjuster, 0.41% dispersant, 0.16% wetting agent, 0.35% defoaming agent, 0.44% rheological additive, 0.8% antifreeze agent, 2.3% film-forming aid, 0.32% mildew and antibacterial agent, and the balance is supplemented by deionized water.
[0058] The waterborne polyurethane emulsion has a solid content of 40% and a viscosity of 1200 mPa·s at 25° C. The product is a Bayhydrol XP 2678 product purchased from Covestro, Germany.
[0059] The filler is ultrafine barium sulfate with an average particle size of 0.25μm.
[0060] The modified particles are modified titanium dioxide; the preparation method of modified titanium dioxide specifically comprises the following steps, calculated by mass: S1: 2.4 parts of titanium dioxide and 2 parts of zinc chloride are mixed and added to 120 parts of DMF solution, 1.1 parts of succinic anhydride are added, the temperature is raised to 75°C and kept warm for 3 hours, after the reaction is completed, diethylamine is added to adjust the pH to 7.5, then 0.24 parts of dodecyl dimethyl benzyl ammonium bromide, 0.35 parts of polyethylene glycol 2000 and 2.2 parts of terephthalic acid are added, the temperature is raised to 120°C and kept warm 26h, the product was filtered, washed with DMF twice, and dried to obtain pre-reacted particles; S2: 2.3 parts of pre-reacted particles, 0.68 parts of 1,4-diaminobenzene, 0.31 parts of p-aminobenzoic acid and 0.14 parts of 2-methylimidazole were mixed and added to 120 parts of DMF, and stirred at 75°C and 240rpm for 18h; S3: Then the temperature was raised to 105°C, and the reaction was kept warm for 16h. After the reaction was completed, the product was filtered, washed with DMF 3 times, and dried in a vacuum oven at 85°C for 8h.
[0061] The average particle size of titanium dioxide is 5.5 nm; the average particle size of modified titanium dioxide is 538 nm.
[0062] The preparation method of the reflective heat-insulating color paste specifically includes the following steps, calculated by mass: S1: adding 60 parts of deionized water to a high-speed mixer, and then adding 2.4 parts of sodium polycarboxylate, 0.8 parts of cocamidopropyl betaine, 0.16 parts of defoamer BYK-066N and 26.5 parts of reflective heat-insulating pigment in sequence, stirring at a speed of 800 rpm for 15 minutes to ensure uniform dispersion, and then adding 2.8 parts of hydroxyethyl cellulose, and adding sodium hydroxide to adjust the pH to 7.5, and then increasing the speed to 1400 rpm to maintain high-speed dispersion for 50 minutes to ensure that the reflective heat-insulating pigment is fully dispersed to form a stable pre-dispersion liquid; S2: transferring the pre-dispersion liquid to a sand mill for sand milling for 90 minutes, and then transferring it to a mixing kettle to add 0.5 parts of sodium polyacrylate, 1.1 parts of propylene glycol and 0.3 parts of thiabendazole, adjusting the stirring speed to 700 rpm, stirring for 25 minutes, and then filtering the mixed product through a 250-mesh sieve to remove large particles of impurities, and sealing and storing.
[0063] The reflective heat-insulating pigment is zinc iron yellow, purchased from Hunan Jufa Pigment Technology Co., Ltd. in China, model PY119.
[0064] The cellulose ether is a composition of hydroxyethyl cellulose and methyl hydroxyethyl cellulose, and the mass ratio of the two is 3.5:1.
[0065] The pH regulator is sodium hydroxide; the dispersant is coconut oil-based betaine.
[0066] The wetting agent is polysiloxane BYK-348; the defoaming agent is silicone defoaming agent BYK-066N.
[0067] The rheological additive is a composition of acrylic acid and hydrogenated castor oil, with a mass ratio of 2.5:5.8. Acrylic acid was purchased from the Acrysol TT-935 model product sold by the Dow Chemical Company of the United States; polyurethane was purchased from the Acrysol 8W model product sold by the Dow Chemical Company of the United States.
[0068] The antifreeze agent is a composition of polyethylene glycol and a nonionic surfactant, and the mass ratio of the two is 3.6:1.4.
[0069] The film-forming aid is a composition of dodecyl alcohol ester and hexadecanol ester, and the mass ratio of the two is 7:2.
[0070] The mildew and antibacterial agent is a composition of benzmethylisothiazolinone and methylisothiazolinone, and the mass ratio of the two is 1.0:1.0.
[0071] The second aspect of the present embodiment provides a method for preparing the above-mentioned reflective heat-insulating water-soluble polyurethane exterior wall coating with integrated waterproof decoration, which specifically includes the following steps: S1: adding deionized water to a mixing container, and then adding filler, modified particles and reflective heat-insulating color paste in sequence, stirring continuously for 35 minutes to ensure uniform dispersion, adding cellulose ether, pH adjuster, dispersant, wetting agent and defoamer, and continuing stirring for 15 minutes, increasing the speed to 1200-1500 rpm, and maintaining high-speed dispersion for 45 minutes to ensure full dispersion and form a stable pre-dispersion liquid; S2: then slowly adding water-based polyurethane emulsion, stirring at 450 rpm while adding to ensure uniform mixing; S3: adding rheological additive, antifreeze agent, film-forming additive and mildew and antibacterial agent, adjusting the stirring speed to 680 rpm, stirring for 25 minutes, and then filtering the mixed product through a 200-mesh sieve to remove large particle impurities, and the filtered coating is divided into clean and dry containers, sealed and stored.
[0072] Example 2 The specific implementation method of this embodiment is basically the same as that of Example 1, with the only difference being that the reflective water-insulating polyurethane exterior wall coating with integrated waterproof decoration has the following raw materials, in terms of mass percentage: 40% water-based polyurethane emulsion, 27% filler, 18% modified particles, 4.5% reflective heat-insulating color paste, 0.4% cellulose ether, 0.22% pH adjuster, 0.41% dispersant, 0.16% wetting agent, 0.35% defoaming agent, 0.44% rheological additive, 0.8% antifreeze agent, 2.3% film-forming aid, 0.32% mildew and antibacterial agent, and the balance is supplemented with deionized water.
[0073] The cellulose ether is a composition of methyl hydroxyethyl cellulose and hydroxyethyl cellulose, and the mass ratio of the two is 3:1.2.
[0074] The rheological additive is a composition of acrylic acid and polyurethane, and the mass ratio of the two is 2:5.5.
[0075] The film-forming aid is a composition of dodecyl alcohol ester and hexadecanol ester, and the mass ratio of the two is 8:1.5.
[0076] Example 3 The specific implementation method of this embodiment is basically the same as that of Example 1, with the only difference being that the reflective water-insulating polyurethane exterior wall coating with integrated waterproof decoration has the following raw materials, in terms of mass percentage: 40% water-based polyurethane emulsion, 32% filler, 13% modified particles, 4.5% reflective heat-insulating color paste, 0.4% cellulose ether, 0.22% pH adjuster, 0.41% dispersant, 0.16% wetting agent, 0.35% defoaming agent, 0.44% rheological additive, 0.8% antifreeze agent, 2.3% film-forming aid, 0.32% mildew and antibacterial agent, and the balance is supplemented with deionized water.
[0077] The cellulose ether is a composition of methyl hydroxyethyl cellulose and hydroxyethyl cellulose, and the mass ratio of the two is 4:1.
[0078] The rheological additive is a composition of acrylic acid and polyurethane, and the mass ratio of the two is 2.5:6.
[0079] The film-forming aid is a composition of dodecyl alcohol ester and hexadecanol ester, and the mass ratio of the two is 6:2.5.
[0080] Comparative Example 1 The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the reflective water-insulating water-based polyurethane exterior wall coating with integrated waterproof decoration, in terms of mass percentage, comprises the following raw materials: 37.5% water-based polyurethane emulsion, 30% filler, 15% modified particles, 4.4% commercially available ordinary color paste, 0.4% cellulose ether, 0.22% pH adjuster, 0.41% dispersant, 0.16% wetting agent, 0.35% defoamer, 0.44% rheological additive, 0.8% antifreeze agent, 2.3% film-forming aid, 0.32% mildew and antibacterial agent, and the balance is supplemented with deionized water.
[0081] Comparative Example 2 The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the reflective water-insulating water-based polyurethane exterior wall coating with integrated waterproof decoration, the raw materials are, by mass percentage: 35% water-based polyurethane emulsion, 30% filler, 18.5% modified particles, 4.4% commercially available ordinary color paste, 0.4% cellulose ether, 0.22% pH regulator, 0.41% dispersant, 0.16% wetting agent, 0.35% defoaming agent, 0.44% rheological additive, 0.8% antifreeze agent, 2.3% film-forming aid, 0.32% mildew and antibacterial agent, and the balance is supplemented with deionized water.
[0082] Comparative Example 3 The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the reflective water-insulating water-based polyurethane exterior wall coating with integrated waterproof decoration, in terms of mass percentage, comprises the following raw materials: 32.5% water-based polyurethane emulsion, 35% filler, 18.5% modified particles, 4.4% commercially available ordinary color paste, 0.4% cellulose ether, 0.22% pH regulator, 0.41% dispersant, 0.16% wetting agent, 0.35% defoaming agent, 0.44% rheological additive, 0.8% antifreeze agent, 2.3% film-forming aid, 0.32% mildew and antibacterial agent, and the balance is supplemented with deionized water.
[0083] Comparative Example 4 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the reflective heat-insulating color paste specifically includes the following steps, measured by mass: S1: add 60 parts of deionized water to a high-speed mixer, then add 1.5 parts of sodium polycarboxylate, 0.2 parts of cocamidopropyl betaine, 0.16 parts of defoamer BYK-066N and 38.8 parts of reflective heat-insulating pigment in sequence, stir at 800 rpm for 15 minutes to ensure uniform dispersion, then add 1.6 parts of hydroxyethyl cellulose, and add sodium hydroxide to adjust the pH to 7.5, then increase the speed to 1400 rpm and maintain high-speed dispersion for 50 minutes to ensure that the reflective heat-insulating pigment is fully dispersed to form a stable pre-dispersion liquid; S2: transfer the pre-dispersion liquid to a sand mill for sand grinding for 90 minutes, then transfer it to a mixing kettle, add 0.2 parts of sodium polyacrylate, 1.1 parts of propylene glycol and 0.3 parts of thiabendazole, and adjust the stirring speed to 700 rpm, stir for 25 min, then filter the mixed product through a 250-mesh sieve to remove large particles of impurities, and seal and store.
[0084] Comparative Example 5 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified titanium dioxide specifically comprises the following steps, calculated by mass: S1: 3.6 parts of titanium dioxide and 1.2 parts of zinc chloride are mixed and added to 120 parts of DMF solution, 1.5 parts of succinic anhydride are added, the temperature is raised to 75°C and kept warm for 3 hours, after the reaction is completed, diethylamine is added to adjust the pH to 7.5, then 0.11 parts of dodecyl dimethyl benzyl ammonium bromide, 0.15 parts of polyethylene glycol 2000 and 1 part of terephthalic acid .... The mixture was heated to 120°C and kept warm for 26 hours. The product was filtered, washed with DMF twice, and dried to obtain pre-reacted particles. S2: 2.3 parts of pre-reacted particles, 0.68 parts of 1,4-diaminobenzene, 0.31 parts of p-aminobenzoic acid and 0.14 parts of 2-methylimidazole were mixed and added to 120 parts of DMF, and stirred at 75°C and 240 rpm for 18 hours. S3: The mixture was heated to 105°C and kept warm for 16 hours. After the reaction was completed, the product was filtered, washed with DMF three times, and dried at 85°C in a vacuum oven for 8 hours to obtain the product.
[0085] The average particle size of the modified titanium dioxide is 411 nm.
[0086] Comparative Example 6 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified titanium dioxide specifically comprises the following steps, calculated by mass: S1: 2.4 parts of titanium dioxide and 2 parts of zinc chloride are mixed and added to 120 parts of DMF solution, 1.1 parts of succinic anhydride are added, the temperature is raised to 75°C and kept warm for 3 hours, after the reaction is completed, diethylamine is added to adjust the pH to 7.5, then 0.24 parts of dodecyl dimethyl benzyl ammonium bromide, 0.35 parts of polyethylene glycol 2000 and 2.2 parts of terephthalic acid .... The mixture was heated to 120°C and kept warm for 26 hours. The product was filtered, washed twice with DMF, and dried to obtain pre-reacted particles. S2: 3.2 parts of pre-reacted particles, 0.28 parts of 1,4-diaminobenzene, 0.11 parts of p-aminobenzoic acid and 0.35 parts of 2-methylimidazole were mixed and added to 120 parts of DMF, and stirred at 75°C and 240 rpm for 18 hours. S3: The mixture was heated to 105°C and kept warm for 16 hours. After the reaction was completed, the product was filtered, washed three times with DMF, and dried at 85°C in a vacuum oven for 8 hours to obtain the product.
[0087] The average particle size of the modified titanium dioxide is 644 nm.
[0088] Comparative Example 7 The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of titanium dioxide is 30 nm; the average particle size of modified titanium dioxide is 787 nm.
[0089] Performance Evaluation Aging resistance test: with reference to standard GB / T 9755-2014, the products prepared in the examples and comparative examples were subjected to 1000h aging resistance test, and the color change value (ΔE) was taken. The test value was the average value of 10 tests and recorded in Table 1.
[0090] Near infrared reflection performance test: The near infrared reflection performance test was performed on the products obtained in the examples and comparative examples with reference to the standard JG / T 235-2014. The test values were recorded in Table 1 by taking the average value of 10 tests.
[0091] Mechanical property test: The tensile strength and elongation at break of the products obtained in the examples and comparative examples were tested with reference to the standard JC / T 864-2023. The test values were recorded in Table 1 as the average values of 10 tests.
[0092] Water resistance test: refer to standard JC / T 864-2023 to carry out water resistance test on the products prepared in the embodiment and comparative example. The test pressure is 0.4 MPa. It is necessary to maintain no water leakage under this pressure for 4 hours. If there is water leakage, it is recorded as unqualified, otherwise it is qualified. 100 groups of samples are tested in each group, and the qualified rate results are recorded in Table 1.
[0093] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that examples 1 to 3 of the present application have obvious advantages over comparative examples 1 to 7 in terms of mechanical properties, waterproof properties, aging resistance, and reflective thermal insulation properties. This is mainly because the modified titanium dioxide used in the examples of the present application can better interact with the waterborne polyurethane system, and can form a good heterojunction structure while absorbing a small amount of light energy. The existence of the structure can greatly enhance the aggregation degree and stability of the oxidized molecules on the surface of the particles, thereby maintaining good impedance of active molecules and organic molecules during long-term use, thereby obtaining excellent corrosion resistance and aging resistance. At the same time, it can also greatly reduce the micropores of the modified particles in the system, reduce the large gaps formed by the pores in series, and thus greatly enhance the barrier effect of the exterior wall coating on moisture and active molecules, thereby maintaining excellent corrosion resistance and other properties.
Claims
1. A reflective water-insulating polyurethane exterior wall coating with integrated waterproof and decorative properties, characterized in that: The raw materials are, in percentage by mass: 30-40% aqueous polyurethane emulsion, 20-30% filler, 8-12% modified particles, 3-6% reflective heat-insulating color paste, 0.3-0.5% cellulose ether, 0.2-0.3% pH adjuster, 0.3-0.5% dispersant, 0.1-0.2% wetting agent, 0.3-0.5% defoamer, 0.3-0.5% rheological additive, 0.3-0.5% antifreeze agent, 0.5-1% film-forming aid, 2-2.5% mildew and antibacterial agent, 0.3-0.6% and the balance is supplemented by deionized water; The solid content of the aqueous polyurethane emulsion is 30-50%; The viscosity of the aqueous polyurethane emulsion is 300-2000 mPa·s, condition: 25°C; The filler is at least one of barium sulfate, calcium carbonate, talc, kaolin and diatomaceous earth; The average particle size of the filler is 0.1-1 μm; The modified particles are modified titanium dioxide; The preparation method of the modified titanium dioxide is specifically The following steps are involved: S1: Mix titanium dioxide and zinc chloride and add them to DMF solution, add succinic anhydride, heat to 70-75℃ and keep warm for 3-3.5h, add diethylamine after the reaction is completed to adjust the pH to 7.5-8, then add dodecyl dimethyl benzyl ammonium bromide, polyethylene glycol 2000 and terephthalic acid, heat to 110-120℃ and keep warm for 24-30h, filter the product, wash with DMF 2-3 times, and dry to obtain pre-reacted particles; S2: Mix the pre-reacted particles, 1,4-diaminobenzene, p-aminobenzoic acid and 2-methylimidazole and add them to DMF, stir at 70-80℃ and 200-300rpm for 16-20h; S3: Then heat to 100-110℃, keep warm for 14-16h, filter the product after the reaction is completed, wash with DMF 2-3 times, and dry at 80-90℃ in a vacuum oven for 6-8h, and obtain the product after completion; The pH regulator is at least one of ammonia water, triethanolamine, sodium hydroxide, 2-amino-2-methyl-1-propanol and triethylamine; The preparation method of the reflective heat-insulating color paste is specifically The following steps are involved: S1: Add deionized water to a high-speed mixer, then add sodium polycarboxylate, cocamidopropyl betaine, defoamer BYK-066N and reflective heat-insulating pigment in sequence, stir at 600-800 rpm for 15-20 min to ensure uniform dispersion, then add hydroxyethyl cellulose and sodium hydroxide solution to adjust the pH to 8-8.5, then increase the speed to 1200-1500 rpm and maintain high-speed dispersion for 40-60 min to ensure that the reflective heat-insulating pigment is fully dispersed to form a stable pre-dispersion liquid; S2: Transfer the pre-dispersed liquid into a sand mill and grind it for 80-100 minutes. Then transfer it into a mixing kettle and add polyurethane rheological additive, propylene glycol and thiabendazole. Adjust the stirring speed to 650-750 rpm and stir for 20-30 minutes. Then filter the mixed product through a 200-300 mesh sieve to remove large particles of impurities and seal it for storage.
2. The reflective water-insulating polyurethane exterior wall paint with integrated waterproof decoration according to claim 1 is characterized in that: The mass ratio of titanium dioxide, zinc chloride and succinic anhydride is (2.3-2.6): (1.8-2.1): (1-1.2); The mass ratio of titanium dioxide, dodecyl dimethyl benzyl ammonium bromide, polyethylene glycol 2000 and terephthalic acid is (2.3-2.6): (0.2-0.25): (0.3-0.4): (2-2.5); The mass ratio of the pre-reacted particles, 1,4-diaminobenzene, p-aminobenzoic acid and 2-methylimidazole is (2.1-2.4): (0.6-0.8): (0.2-0.4): (0.1-0.2).
3. The reflective water-insulating polyurethane exterior wall paint with integrated waterproof decoration according to claim 2 is characterized in that: The average particle size of the titanium dioxide is 5-10 nm; the average particle size of the modified titanium dioxide is 500-600 nm.
4. The reflective water-insulating polyurethane exterior wall paint with integrated waterproof decoration according to claim 3 is characterized in that: The mass ratio of the aqueous polyurethane emulsion, filler and modified particles is (32-38): (22-26): (10-12).
5. The reflective water-insulating polyurethane exterior wall paint with integrated waterproof decoration according to claim 4 is characterized in that: The cellulose ether is a composition of methyl hydroxyethyl cellulose and hydroxyethyl cellulose; the mass ratio of the methyl hydroxyethyl cellulose to the hydroxyethyl cellulose is (3-4): (1-1.2).
6. The reflective water-insulating polyurethane exterior wall paint with integrated waterproof decoration according to claim 5 is characterized in that: The dispersant is at least one of polycarboxylate sodium salt, polycarboxylate ammonium salt, lauryl alcohol polyoxyethylene ether, cetearyl alcohol polyoxyethylene ether and coconut oil betaine.
7. The reflective water-insulating polyurethane exterior wall paint with integrated waterproof decoration according to claim 6 is characterized in that: The rheological additive is a composition of acrylic acid and polyurethane; the mass ratio of acrylic acid to polyurethane is (2-2.5): (5.5-6).
8. The reflective water-insulating polyurethane exterior wall paint with integrated waterproof decoration according to claim 7 is characterized in that: The antifreeze agent is at least one of polyethylene glycol, propylene glycol, glycerol, diethylene glycol and a nonionic surfactant.
9. The reflective water-insulating polyurethane exterior wall paint with integrated waterproof decoration according to claim 8, characterized in that: The film-forming aid is a composition of dodecyl alcohol ester and hexadecanol ester; the mass ratio of the dodecyl alcohol ester to the hexadecanol ester is (6-8): (1.5-2.5).
10. A method for preparing the reflective water-insulating water-soluble polyurethane exterior wall coating with integrated waterproof decoration according to any one of claims 1 to 9, characterized in that: S1: Add deionized water to a mixing container, add filler, modified particles and reflective insulation color paste in turn, continue stirring for 30-40 minutes to ensure uniform dispersion, add cellulose ether, pH adjuster, dispersant, wetting agent and defoamer, continue stirring for 15-20 minutes, increase the speed to 1200-1500 rpm, maintain high-speed dispersion for 30-60 minutes to ensure full dispersion and form a stable pre-dispersion liquid; S2: Then slowly add water-based polyurethane emulsion, stirring at 400-500 rpm while adding to ensure uniform mixing; S3: Add rheological additive, antifreeze agent, film-forming additive and mildew and antibacterial agent, adjust the stirring speed to 650-750 rpm, stir for 20-30 minutes, then filter the mixed product through a 100-200 mesh screen to remove large particles of impurities, and divide the filtered coating into clean and dry containers, seal and store.
Citation Information
Patent Citations
High infrared reflectance ratio aqueous building coating color paste and preparation method thereof
CN103642322A
Waterborne polyurethane heat reflection heat insulation external wall paint and preparation method thereof
CN108485362A
Waterborne polyurethane waterproof coating with excellent heat insulation and reflection properties and preparation method thereof
CN113337196A
Cerium oxide reflective insulation color paste and preparation method thereof
CN113637363A
Heat insulation rock slice
CN116445069A